Reinventing the Human Dignity in Islamic Law Discourse: The Wasatiyah Approaches from Khaled Abou El-Fadl to the Interreligious Relation - Wildani Hefni; Rizqa Ahmadi; Imam Mustofa (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2022)
Violence in the name of religion has never completely disappeared from discourse on religious life. Surprisingly, Islamic law is used as the basis for committing acts of violence damaging interreligious relations. There is a gap between the goals of Islamic law and practice in society. This article aims to unpack the wasatiyah approach provided by Khaled Abou El-Fadl in Islamic law discourses. This research is a qualitative method using library research, which obtains information from books, articles, and journals. This research concludes that El-Fadl provides an essential concept known in contemporary Islamic law as al-wasatiyah by integrating various scientific disciplines to strengthen human dignity. El-Fadl offers a moderate-humanist approach as a system that is considered more holistic and comprehensive in Islamic law, especially in constructing texts, understanding the context, and optimizing legal reasoning based on maqasid al-shariah through independent reasoning. This article shows that El-Fadl allows greetings to non-Muslims, greetings of Christmas to non-Muslims, interacts with non-Muslims, and elects non-muslim leaders. El-Fadl believes in strengthening the theological basis of pluralism, which requires tolerance as a pathway for creating a mutually productive life together.